Repair of O6-carboxymethylguanine adducts by O6-methylguanine-DNA methyltransferase in human colon epithelial cells. (11th June 2021) - Kostka, Tina; Empl, Michael T; Seiwert, Nina; Geisen, Susanne M; Hoffmann, Pascal; Adam, Janine; Seeger, Bettina; Shay, Jerry W; Christmann, Markus; Sturla, Shana J; Fahrer, Jörg; Steinberg, Pablo
Abstract: The protein O 6 -methylguanine-DNA methyltransferase (MGMT) is able to repair the mutagenic O 6 -methylguanine ( O 6 -MeG) adduct back to guanine. In this context, it may protect against colorectal cancer formation associated with N -nitroso compounds. Such compounds may be endogenously formed by nitrosylation of amino acids, which can give rise to mutagenic O 6 -MeG and O 6 -carboxymethylguanine ( O 6 -CMG) adducts. It is well established that O 6 -MeG is repaired by MGMT. However, up to now, whether O 6 -CMG is repaired by this enzyme remains unresolved. Therefore, the aim of the present study was to analyze the fate of both types of O 6 -guanine adducts in the presence and absence of MGMT activity. To this end, MGMT activity was efficiently blocked by its chemical inhibitor O 6 -benzylguanine in human colon epithelial cells (HCECs). Exposure of cells to azaserine (AZA) caused significantly higher levels of both O 6 -MeG and O 6 -CMG adducts in MGMT-inhibited cells, with O 6 -CMG as the more abundant DNA lesion. Interestingly, MGMT inhibition did not result in higher levels of AZA-induced DNA strand breaks in spite of elevated DNA adduct levels. In contrast, MGMT inhibition significantly increased DNA strand break formation after exposure to temozolomide (TMZ), a drug that exclusively generates O 6 -MeG adducts. In line with this finding, the viability of the cells was moderately reduced by TMZ upon MGMT inhibition, whereas no clear effect was observed in cells treated with AZA. In conclusion, our study clearly shows that O 6 -CMG is repaired by MGMT in HCEC, thereby suggesting that MGMT might play an important role as a tumor suppressor in diet-mediated colorectal cancer.